High-performance work practices and employee attitudes - Kengatharan, N.; Rajeetha, M. (Eastern University, 2019)
Drawing on social information processing theory and social exchange theory, the present study aims to establish the relationship between high-performance work practices, and job satisfaction and organisational commitment. In line with strong ontological and epistemological assumptions, the study adopts survey strategy with a deductive approach. Data were garnered from randomly selected employees working in Capital Reliance Investments (Pvt) Ltd with a self-administered questionnaire. The results disclose a significant positive relationship between high-performance work practices and job satisfaction. Similarly, the study reveals a strong relationship between high-performance work practices and organisational commitment. The current study advances the extant knowledge in the spheres of high-performance work practices and employee attitudes, and proffers many useful practical implications.
Keywords: High-performance work practice; job satisfaction; Oorganisational commitment; Social exchange theory; Social information processing theory